113. Spinal Direct Current Stimulation modulates short intracortical inhibition. Issue 4 (April 2016) - Barloscio, D.; Bocci, T.; Bartolotta, M.; Parenti, L.; Vannini, B.; Di Rollo, A.; Sartucci, F.
Abstract : Transcutaneous spinal Direct Current Stimulation (tsDCS) is a new and safe technique for modulating spinal cord excitability. We evaluated healthy subjects before (T0) and at different intervals (T1 and T2) after anodal, cathodal and sham tsDCS (20 ′, 2.0 mA) applied over the thoracic spinal cord (T10–T12). We assessed changes in cortical Silent Period (cSP), paired-pulse short intracortical inhibition (SICI, interstimulus interval, ISI = 3 ms) and intracortical facilitation (ICF, ISI = 10 ms). Motor Evoked Potentials (MEPs) were recorded from first digital interosseus (FDI) and tibialis anterior (TA) muscles. Cathodal tsDCS increased MEP amplitudes at ISI of 3 ms, while anodal one elicited opposite effects (FDI: p  = 0.0023; TA: p  = 0.0004); conversely, tsDCS left MEP amplitudes unchanged at ISI of 10 ms (FDI: p  = 0.39; TA: p  = 0.45). No significant change in cSP duration was found from upper ( p  = 0.81) and lower limb ( p  = 0.33). tsDCS modulates inhibitory GABA(A) ergic drive, as assessed by SICI, without interfering with cSP and ICF. tsDCS may be helpful to modulate spinal drive through non spinal mechanisms. tsDCS could represent an early rehabilitation strategy in patients with acute brain lesions and in the treatment of spinal diseases or pain syndromes.